2015
DOI: 10.5009/gnl14231
|View full text |Cite
|
Sign up to set email alerts
|

Role of Balloon-Sheathed Intraductal Ultrasonography for Patients with Extensive Pneumobilia

Abstract: Intraductal ultrasonography (IDUS) is one of the most useful diagnostic tools for various extrahepatic biliary diseases. However, conventional IDUS has some limitations in providing accurate cross-sectional imaging of the bile duct in patients with extensive pneumobilia. Using a balloon-sheathed catheter, the US system (balloon-sheathed IDUS) can overcome these limitations. Sixteen patients underwent balloon-sheathed IDUS during endoscopic retrograde cholangiography. The balloon-sheathed IDUS was inserted via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, the authors suggested that a guidewire assisted, larger balloon-tipped mini-probe would be more effective and attractive. [ 38 ]…”
Section: Evaluation Of Choledocholithiasismentioning
confidence: 99%
“…Therefore, the authors suggested that a guidewire assisted, larger balloon-tipped mini-probe would be more effective and attractive. [ 38 ]…”
Section: Evaluation Of Choledocholithiasismentioning
confidence: 99%